Development of an Energy Complex of Wind Farms and Thermal Power Plants in China - Qiujin Zhu; Oleg Yu. Sigitov (RUDN Journal of Engineering Research)
China is undergoing a transformation of its energy system to meet the goals of pollutant reduction and carbon neutrality. The integration of renewable energy sources into the existing energy system is a subject of considerable relevance. The initial phase of the study involved the development of a map showing potential sites for wind farms. Consequently, the locations exhibiting the highest and lowest levels of wind energy potential were identified. The second part of the study is based on an analysis of the current status of China’s energy system and wind energy potential. It considers a model of an integrated energy complex combining wind farms and coal-fired thermal power plants. In order to develop such complex systems, it is necessary to consider the unstable operation modes of wind farms, in order to ensure that maximum energy consumption is covered. The findings of the study demonstrate that such a complex can play a significant role in optimizing the power structure, improving grid stability and reducing pollutant emissions, providing an effective solution for China’s energy strategy.